Six Degrees of Film, Social, and Cultural History:: The Fogo Island Film Project of 1967 and the "Newfoundland Renaissance" - Newhook, Susan (Acadiensis, 2010)
Abstract The Fogo Island film partnership of the National Film Board and the Memorial University of Newfoundland Extension Service helped establish a fisheries cooperative on Fogo Island and, in the process, a template for the NFB’s Challenge for Change program. The Fogo Island films have achieved near-mythic status in film studies and film history as a coup for the NFB, but the role of the Newfoundland partners has been largely ignored. This article addresses this gap in the literature, and traces how the project and the process behind it helped to spark the "cultural revolution" of the 1970s in Newfoundland and Labrador.